Problems of interpreting the main types of hadith in terms of their correct understanding - Abdullaieva, Tamila; Gafuri, Rustam; Akhatov, Hasan; Aga, Khaisam (Linguistics and Culture Review, 2021)
The methodology for analysing the veracity and accuracy of the hadith of the Prophet Muhammad involves a set of specific procedures and activities. The science of hadith helps to clearly assess each individual expression attributed to the Prophet Muhammad in terms of its veracity. The task of hadith scholars is to determine the truth of hadith. Only after examining the biographies of the people mentioned in the Isnad (chain of transmissions) to convince them of their positive moral and intellectual qualities it is possible to judge the authenticity of a particular hadith. The purpose of the study was to conduct a systematic analysis of the stages of hadith study based on Sheikh Abdullah Harare’s theology and to draw attention to the complexity of the science of hadith. This study provides traditional insights into the hadith and Sunnah of the Prophet Muhammad as an important source of Islamic religion and Muslim culture in general. All the Prophet’s activities are covered by the Sunnah, which was, remains and will remain one of the main sources of Muslim law, secondary solely to the Holy Koran.